Pyrophosphate Scintigraphy and other Non-Invasive Methods in the Detection of Cardiac Involvement in Some Systemic Connective Tissue Diseases - Duška, F.; Bradna, P.; Pospíšil, M.; Kubíček, J.; Vižda, J.; Kafka, P.; Palička, V.; Mazurová, Y. (Nuklearmedizin - NuclearMedicine, 1987)
Thirteen patients with systemic lupus erythematosus, 8 patients with polymyositis, and 6 patients with spondylitis ankylopoetica (Bechterew’s disease) underwent clinical cardiologic examination and scintigraphy of the myocardium (99mTc-pyrophosphate), ECG, echocardiography, polygraphy, and their blood pressure was taken. The aim of the study was to ascertain how such a combination of non-invasive examinations can help in recognizing a cardiac involvement. In systemic lupus erythematosus cases one or more positive findings were revealed in 9 patients (69%), in 4 patients all examinations were negative (31 %). Four patients (50%) with polymyositis had positive findings. In patients with spondylitis ankylopoetica positive findings occurred in 2 cases (33%). The study has shown that a combination of non-invasive cardiologic methods increases the probability of detecting cardiac involvement in systemic connective tissue diseases.Bei 13 Patienten mit systemischem Lupus erythematodes, 8 Patienten mit Polymyositis und 6 Patienten mit Spondylarthritis ankylopoëtica (Morbus Bechterew) wurden eine klinische kardiologische Untersuchung, ferner Myokard-Szintigraphie (99mTc-Pyro- phosphat), EKG, Echokardiographie, Polygraphie und Messung des Blutdrucks vorgenommen. Das Ziel der Arbeit war es, festzustellen, inwieweit eine derartige Kombination von nichtinvasiven kardiologischen Untersuchungen zur Ermittlung der kardialen Mitbeteiligung beitragen kann. Im Falle des Lupus erythematodes wurden einer bzw. mehrere positive Be-funde bei 9 Patienten (69%) erhoben; bei 4 (31%) waren alle Untersuchungen negativ. Bei 4 Patienten mit Polymyositis (50%) wurde ein positiver Befund erhoben. Bei den Patienten mit Spondylarthritis ankylopoetica ist der Befund bei 2 Fällen (33%) positiv ausgefallen. Diese Ergebnisse zeigen, daß die Kombination von nichtinvasiven kardiologischen Methoden die Wahrscheinlichkeit des Nachweises der Herzbeteiligung bei den Systemerkrankungen des Bindegewebes erhöht.